The risk of major cardiovascular events for adults with transfemoral amputation - Mundell, Benjamin F. (J Neuroeng Rehabil, 2018)
BACKGROUND: It is well-known that the risk of cardiac disease is increased for those with lower-limb amputations, likely as a result of the etiology of the amputation. Using a longitudinal population-based dataset, we examined the association between transfemoral amputation (TFA) status and the risk of experiencing a major cardiac event for those undergoing either dysvascular or traumatic amputations. The association of receiving a prosthesis with the risk of experiencing a major cardiac event was also examined. METHODS: Study Population: All individuals with TFA (N 162), i.e. knee disarticulation and transfemoral amputation, residing in Olmsted County, MN, between 1987 and 2014. Each was matched (1:10 ratio) with non-TFA adults on age, sex, and duration of residency. Data Analysis: A competing risk Cox proportional hazard model was used to estimate the relative likelihood of an individual with a TFA experiencing a major cardiac event in a given time period as compared to the matched controls. The cohort was divided by amputation etiology: dysvascular vs trauma/cancer. Additional analysis was performed by combining all individuals with a TFA to look at the relationship between prosthesis receipt and major cardiac events. RESULTS: Individuals with a dysvascular TFA had an approximately four-fold increased risk of a cardiac event after undergoing an amputation (HR 3.78, 95%CI: 3.07–4.49). These individuals also had an increased risk for non-cardiac mortality (HR 6.27, 95%CI: 6.11–6.58). The risk of a cardiac event was no higher for those with a trauma/cancer TFA relative to the able-bodied controls (HR 1.30, 95%CI: 0.30–5.85). Finally, there was no difference in risk of experiencing a cardiac event for those with or without prosthesis (HR 1.20, 95%CI: 0.55–2.62). CONCLUSION: The high risk of initial mortality stemming from an amputation event may preclude many amputees from cardiovascular disease progression. Amputation etiology is also an important factor: cardiac events appear to be more likely among patients with a dysvascular TFA. Providing a prosthesis does not appear to be associated with a reduced risk of a major cardiac event following amputation.